2015
DOI: 10.1016/j.drugalcdep.2015.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic cannabinoid use in a nationally representative sample of US high school seniors

Abstract: Background Synthetic cannabinoids are marketed as “legal highs” and have similar effects to cannabis (marijuana). Although prevalence of synthetic cannabinoid use is now declining in the US, use has been associated with tens of thousands of poisonings and hospitalizations, particularly among teens. It is important to examine which teens are at highest risk for use of these new, potentially deleterious drugs as they are understudied and continue to emerge. Methods Data were analyzed from a nationally represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 31 publications
9
68
0
Order By: Relevance
“…The reasons for SCs' use are normally their better availability, avoiding positive screening on a drug test and their lower cost [20,45]. However, the frequency of marijuana use appears to increase the likelihood of SCs' use [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for SCs' use are normally their better availability, avoiding positive screening on a drug test and their lower cost [20,45]. However, the frequency of marijuana use appears to increase the likelihood of SCs' use [43].…”
Section: Discussionmentioning
confidence: 99%
“…In general, most users prefer natural marijuana over SCs since it tends to be associated with fewer adverse effects [15,22,37], so the majority of SC use is experimental [43].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SCs toxicity reports in the United States increased from 349 in January, 2015, to 1501 in April of the same year (Law, Schier, Martin, Chang & Wolkin, 2015). Likewise, a study performed in the United States on a sample of 12000 adolescents found that up to 10% of the students had used SCs in the previous 12 months and 3.2% acknowledged a frequent use of at least six times in the same time frame (Palamar & Acosta, 2015).…”
Section: Synthetic Cannabinoidsmentioning
confidence: 99%
“…13 Furthermore, whereas overall rates of SC use have declined, research has shown that rates of SC use among routine marijuana users has decreased at a much slower rate than their nonusing and lessfrequent marijuana-using peers. 14 15,17 Notably, studies to date do not assess whether marijuana use is predictive of SC use or vice versa. Given that marijuana is the most commonly used illicit drug by high school students in the United States, 11 it is important to delineate the temporal relations between these variables to inform adolescent substance-use and prevention efforts.…”
mentioning
confidence: 99%